2011
DOI: 10.1007/s00344-011-9244-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salinity on Metabolic Profiles, Gene Expressions, and Antioxidant Enzymes in Halophyte Suaeda salsa

Abstract: Halophyte Suaeda salsa is native to the saline soil in the Yellow River Delta. Soil salinity can reduce plant productivity and therefore is the most important factor for the degradation of wetlands in the Yellow River Delta. In this work we characterized the salinity-induced effects in S. salsa in terms of metabolic profiling, antioxidant enzyme activities, and gene expression quantification. Our results showed that salinity inhibited plant growth of S. salsa and upregulated gene expression levels of myo-inosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 50 publications
4
32
0
Order By: Relevance
“…For the above-ground part of S. salsa seedlings, decreased intermediates, succinate and fumarate, in tricarboxylic acid (TCA) cycle showed the disturbances in TCA cycle that is related to energy metabolism (Zhang et al, 2011). The increased amino acids and decreased total protein suggested that protein biodegradation was enhanced in S. salsa caused by Hg treatment (Wu et al, 2012;Dai et al, 2010). In plant cells, sugars such as glucose, fructose and sucrose, are commonly derived from photosynthesis and gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the above-ground part of S. salsa seedlings, decreased intermediates, succinate and fumarate, in tricarboxylic acid (TCA) cycle showed the disturbances in TCA cycle that is related to energy metabolism (Zhang et al, 2011). The increased amino acids and decreased total protein suggested that protein biodegradation was enhanced in S. salsa caused by Hg treatment (Wu et al, 2012;Dai et al, 2010). In plant cells, sugars such as glucose, fructose and sucrose, are commonly derived from photosynthesis and gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In plant cells, sugars such as glucose, fructose and sucrose, are commonly derived from photosynthesis and gluconeogenesis. Hereby, decreased glucose might imply that photosynthesis and/or gluconeogenesis were/was inhibited by Hg exposure in S. salsa (Wu et al, 2012). Ferulate is one of the phenolic acids in plants, occurring in seeds and leaves (Mathew and Abraham, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Extraction analysis of S. corniculata leaf tissue was performed with a Bruker AV 500 NMR spectrometer at 500.18 MHz (at 298 K) (Wu et al 2012). One dimensional (1D) 1 H NMR spectra were obtained with the following parameters: 11.9 μs pulse, 6009.6 Hz spectral width, 0.1 s mixing time, and 3.0 s relaxation delay with standard 1D NOESY pulse sequence, with 128 transients collected into 16,384 data points.…”
Section: Nmr Analysismentioning
confidence: 99%
“…More than twenty species of Suaeda have been reported for their ability to survive high salt conditions, including S. salsa (Zhang and Zhao 1998), S. maritima (Maathuis et al 1992;Wetson and Flowers 2010), S. aegyptiaca (Askari et al 2006), S. asparagoides (Ayarpadikannan et al 2012), S. fruticosa (Khan and Ungar 1998), S. glauca (Yang et al 2008b, S. physophora (Song et al 2006) and S. corniculata (Wei et al 2012). In particular, recent studies of salt responsive physiology, molecular genetics, proteomics and metabolomics in S. salsa have yielded more information for understanding the complex mechanisms of Suaeda plants' salt response and tolerance (Zhang et al 2001;Lu et al 2003;Pang et al 2005;Han et al 2011;Li et al 2011Li et al , 2011bWu et al 2012). In previous studies of S. salsa, salt treatment caused the up-regulation of aquaporin (Qi et al 2009), vacuolar Na + /H + antiporter (Qiu et al 2007), V-ATPase and V-PPase , indicating that Suaeda can maintain homeostasis in water potential and ion distribution by increasing leaf succulence and compartmenting the ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation